Industry 5.0: Spectrum or Entity? - Gupta , Sanjiv (Gyan Management Journal, 2023)
The fast pace of innovation in technology is shrinking the world. The digital technology of Industry 4.0 has reduced the role of human beings and boosted automation. The world is on the threshold of using technology of industry 5.0 commercially with the advantage of human interaction from the technology of Industry 4.0. This research paper analyses the current state of industry 4.0 and future implications of industry 5.0 in the dynamic business environment. One emerging theme is Human- Robot coworking. There is an emphasis on sustainable and resilient production systems. The main aim of the researcher is to determine whether industry 5.0 is truly human centric and also to look at the changes the first and third world countries are likely to face during the implementation of industry 5.0. with the aim of achieving sustainable processes.